STUDI NUMERIK SEPARASI ALIRAN 3D AKIBAT PENAMBAHAN FFST PADA BIDANG TUMPU AIRFOIL ASIMETRI - Nurjannah, Ika; Sasongko, Herman; Mirmanto, Heru (Otopro, 2020)
3D flow separation is a form of flow loss that cannot be avoided on turbo engines. In the axial compressor, 3D flow separation is due to the interaction between the blade boundary layer and the casing boundary layer or the hub boundary layer. The result of the secondary flow causes blockage of the flow which causes the pressure on the compressor to decrease. Efforts to reduce secondary flow are carried out by adding a FFST to endwall. This research was conducted in a numerical simulation using FLUENT 6.3.26 software. The parameters used in the free stream flow Re = 1.64 x 105 and Turbulence Intensity Tu = 0.3% to assess the comparison of the flow characteristics on the endwall of the British 9C7 / 22.5C50 asymmetric airfoil due to the addition of a FFST and without FFST with variations angle of attack (Î±) of 00, 80, 120, 140, 160 .The results show that the addition of FFST can increase the turbulent intensity in the area near the wall which turns into momentum, so that it has an impact on the ability of the flow to overcome the adverse pressure in the trailing edge area and further backward (delayed) separation which results in smaller wake. With the addition of the angel of attack, the saddle point position is more directed to the lower side and the attachment line is not induced by the horseshoe vortex, so that the flow is more able to follow the contours of the body, as a result the curling flow is weaker and the wake is narrower and the blockage (energy loss) can be reduced. The most effective energy reduction due to secondary flow through FFST occurs at Î± = 8 Â° at 7.36%.